Building Creativity Beyond The Classroom: The 4DFrame After-School Experience In Bandung, Indonesia - Alfiansah Sandion Prakoso; Anti Haryanti; Irma Rahma Suwarma (Jurnal Kajian Pendidikan IPA, 2026)
Creativity is an important life skill but is often underemphasized in formal education due to curriculum limitations. Extra-curricular programs can provide alternative opportunities to develop these skills. This study aims to analyze the learning process and creativity outcomes of the Young STEM Program using 4DFrame as learning media. A descriptive study was conducted involving 17 students who participated in this after-school program for three months. Student creativity was assessed based on a product design worksheet and final product using rubric adapted from Torrance framework, which includes 4 aspects namely fluency, flexibility, originality, and elaboration. The result showed an increase in overall creativity, especially in the aspect of fluency and elaboration, as evidenced by a shift in student’s performance from lower to higher rubric categories. By the final topic, 71% of students reached an excellent level in fluency, while all students achieved at least a good level in elaboration. Meanwhile, flexibility and originality aspects are still varying depending on the topic given. These findings suggest that structured extracurricular/after-school STEM activities using tools such as 4DFrame can support the development of specific aspects of student creativity.Keywords: 4DFrame, After-school program, Creativity, STEM education